2017
DOI: 10.1002/hipo.22760
|View full text |Cite
|
Sign up to set email alerts
|

Early survival and delayed death of developmentally‐born dentate gyrus neurons

Abstract: The storage and persistence of memories depends on plasticity in the hippocampus. Adult neurogenesis produces new neurons that mature through critical periods for plasticity and cellular survival, which determine their contributions to learning and memory. However, most granule neurons are generated prior to adulthood; the maturational timecourse of these neurons is poorly understood compared to adult-born neurons but is essential to identify how the dentate gyrus (DG), as a whole, contributes to behavior. To … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 92 publications
(147 reference statements)
6
44
0
Order By: Relevance
“…We therefore adjusted our criterion to include only cells that were unambiguously, strongly labeled with BrdU (≥50% of the nucleus stained). We found that ~150,000 granule neurons were born on P6, and there was a 15% loss of BrdU + cells between 2 and 6 months of age, replicating our previous findings (Cahill et al, 2017). Thus, this is likely a more accurate estimate of the true E19 value.…”
Section: Re Sultssupporting
confidence: 88%
See 3 more Smart Citations
“…We therefore adjusted our criterion to include only cells that were unambiguously, strongly labeled with BrdU (≥50% of the nucleus stained). We found that ~150,000 granule neurons were born on P6, and there was a 15% loss of BrdU + cells between 2 and 6 months of age, replicating our previous findings (Cahill et al, 2017). Thus, this is likely a more accurate estimate of the true E19 value.…”
Section: Re Sultssupporting
confidence: 88%
“…Since these numbers were comparable to our previous counts of P6-born cells (Cahill et al, 2017), and previous reports have indicated that prenatal neurogenesis is substantially lower than early postnatal neurogenesis (Bayer & Altman, 1974;Schlessinger et al, 1975), this criterion likely included many cells that were labeled by redivision and overestimated the true value. Since these numbers were comparable to our previous counts of P6-born cells (Cahill et al, 2017), and previous reports have indicated that prenatal neurogenesis is substantially lower than early postnatal neurogenesis (Bayer & Altman, 1974;Schlessinger et al, 1975), this criterion likely included many cells that were labeled by redivision and overestimated the true value.…”
Section: Re Sultssupporting
confidence: 77%
See 2 more Smart Citations
“…The dentate gyrus of the hippocampus is an attractive model to study homeostasis of immature neurons, since dentate granule cells (GCs) are born and differentiate postnatally, both in vivo (Altman and Das, 1965; van Praag et al, 2002; Toni et al, 2007; Kempermann et al, 2015; Nicola et al, 2015; Cahill et al, 2017; Radic et al, 2017a) and in vitro (Raineteau et al, 2004; Radic et al, 2017b). Previous work has demonstrated that immature GCs are capable of expressing Hebbian forms of synaptic plasticity, i.e., long-term potentiation (LTP) of excitatory synaptic strength (e.g., Schmidt-Hieber et al, 2004; Gonçalves et al, 2016).…”
Section: Introductionmentioning
confidence: 99%